Internet and Facebook use among university students - Phua, Susan; Wong, Su Luan (School of Graduate Studies, Universiti Putra Malaysia, 2015)
The Malaysian government continues to invest heavily in computing and Internet resources in the belief that the Internet can improve the academic performance of students, offer e-learning for undergraduates, and provide the flexibility of distance learning for adult students. The use of the Internet and Facebook for educational purposes has been a topic of high interest among researchers in recent years. In Malaysia, Internet access is relatively easy, fast, and affordable. It is also a valuable source of information. Research shows that online consumers in Malaysia, Thailand and the Philippines are the most likely to have engaged on social media sites such as Facebook. For this very reason, students must be well-equipped with the requisite skills to exploit to the full the benefits of the Internet and Facebook by the time they graduate. Such skills would certainly help to enhance their employability in the competitive labour market. This study seeks to examine relevant literature regarding the extent of Internet and Facebook use among university students. The literature review will also explore how the use of the Internet and Facebook has impacted the academic performance of university students.